THE EFFECT OF E-SPT AND NATIONAL TAX CENSUS ON THE INCOME OF INCOME TAX (Case Study in West Java Regional Tax Office 1) - Kartika Merdeka Wati; Asep Kurniawan; Sri Mulyati (STIESA Press, 2019)
This research aims to know the influence of e-SPT and National Tax Census (NTC) of the Personal Income Tax receipts partially or simultaneously. Data obtained come from the Kanwil DJP West java 1. Data taken from 2012 to 2013, includes user e-SPT, the addition of the number of taxpayers, and acceptance of The Personal income tax. The method of sample selection the sample selection technique used nonprobability sampling and saturated samples, which taken as a whole than 15 (fifteen) work unit KPP. Types of data used by researchers that quantitative data and data sources in this study is secondary data. Before performing hypothesis testing, data obtained in advance a classic assumption test tested. Hypothesis testing is carried out by means of multiple linear regression in statistical analysis. As for the results of the study are as follows: 1) partially e-SPT effect negatively to personal income tax reception. While the NTC does not affect the acceptance of personal income tax. 2) simultaneously e-SPT and NTC effect on receipt of The personal income tax.